Screening for SARS-CoV-2 via PCR and serological testing in asymptomatic healthcare workers. Issue 4 (4th July 2021) - Safder, Taimur; McCullough, Peter A.; Wheelan, Kevin R.; Rahimi, Gelareh; Zurawski, Sandra; Zurawski, Gerard; Gu, Jinghua; Wang, Xuan; Balaji, Uthra; Berhe, Mezgebe; Clariday, Laura; Baker, Rebecca; et al.
Abstract: The prevalence and seroconversion rate of SARS-CoV-2 infection among asymptomatic health care workers in the US is unclear. Our study utilized real-time polymerase chain reaction (RT-PCR) SARS-CoV-2 testing and serological evaluation to detect IgG antibodies specific to SARS-CoV-2 antigens in asymptomatic health care workers. A total of 197 subjects with a mean age of 35 years were recruited into the study. While most (67%) reported prolonged contact with known COVID-19 patients, only 8 (4.2%) tested positive on RT-PCR and 23 (11.7%) had detectable levels of IgG antibody to SARS-CoV-2. Out of 19 subjects with detectable IgG antibody at week 1, 11 (57.9%) lost their antibody response by week 3. No statistically significant difference was found in baseline characteristics or exposure status between subjects with positive and negative results on RT-PCR or antibody positivity. In conclusion, we found a low incidence of PCR positivity for SARS-CoV-2 in a high-risk group. This likely demonstrates the effectiveness of proper personal protective equipment use and low transmission risk in health care settings. The detectable IgG antibody titer was low, and a significant portion of subjects lost their antibody response on repeat testing. This may mean that antibody response in asymptomatic patients is categorically different than in symptomatic hospitalized patients with COVID-19.